(untitled) (Journal of the College of Basic Education, 2023)
A study titled ““The psychosocial factors that affecting the learning of students. ”. this study aimed to identifying the main psycho-sociological factors that play big roles in facilitating or distraction the learning process between teachers and students. And to find out the ways of managing and solving problems that distract students learning. There are a lot of psychosocial factors that affecting the student’s ability to learn like: family factors (parent’s separation, home environment), class factors (studying with close friends, taking class together boys and girls, having exam before or after the class), the teacher’s strategy and teaching style and the college or institute’s strict rules, as well as the class room atmosphere. Questionnaire included three parts. 1st part included 13 questions covering the above mentioned psychosocial factors from student points of view that have been answered by the students through interview. 2nd part of questionnaire included two essay questions allocated to be answered by the student him/herself, which were (1. What you will do if you were assigned in class which you don’t like the students and teachers at that class?) and (2. According to your opinion what are the important psychosocial factors that promote or obstruct your learning?). And finally the 3th part, students were asked to rank the psychosocial factors that were mentioned above according to the priority. (93) in (69.4% ) from the total number of the third year students (134) from College of Health Science at Sultan Quboos University / Muscat / Oman, were chosen and interviewed randomly to answer structured questionnaire of three parts. (55.9%) of the sample were male and (44.1%) were female. (94.6%) of students from both sexes were Omani and only 5 in (5.4%) female students were from Arab Gulf Countries. 48% of the male and 61% of the female was living in the dorm including the 5 female students from Arab Gulf Countries. (14) in (15.1%) male and female students raised by single parents because of the death of one parent or divorce. Data were analyzed. Likert Scale was used for rating (agree, neither agree nor disagree, and finally disagree). Students were ranking the psychosocial factors from their point of view and the result were revealed as follows: (67.35%) of them considered that family affairs taken 1st priority as a factor effecting students learning, followed by college rules and regulation in( 45.85% ) , then Friends relation ( 44.4% ) then teacher ability to teach ( 40.2% )and finally class atmosphere in ( 37.45% ). All teachers and students as well as college students affairs and social workers should cooperate together to be part of the solution and facilitator the teaching learning process. The researcher recommended that “social workers unit” in each college should be established in order to create a relation between university / college and student’s family to understand students life at home and help in facilitating students learning